Peningkatan Kualitas Penulisan Artikel Ilmiah bagi Kepala Sekolah - Zadrian Ardi; Erlamsyah Erlamsyah; Ifdil Ifdil (Jurnal Aplikasi IPTEK Indonesia, 2017)
The principal as a social worker has thousands and even millions of aspects and scope of scholarship that can be used as material for scientific development, especially related to the development of learning process and improvement of learning. As a professional, social workers including counselors, psychologists and policy-makers such as principals are urgently needed to develop their insights and knowledge of human and territorial behavior that can be addressed through counseling services. Various things will certainly be realized by the research or research and publish through scientific articles. But in reality, the principal has not been too concerned and develop the ability and competence in the field of scientific articles. Various cases and services that should be used as material for scientific and professional discussions are not published in the form of scientific articles so that in general the parameters of the development of learning and service BK in the school can not be known with certainty. These conditions require the principal to have the competence and skills in writing scientific articles and using digital citation program / software.